Edukasi Digitalisasi Usaha dan Inovasi Kemasan Ramah Lingkungan bagi UMKM Kelurahan Ketapang - Kus Andini Purbaningrum; Barra P. Pradja; Agus Yulistiyono (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Ketapang District, Tangerang City, still face limitations in utilizing digital marketing and adopting environmentally friendly packaging, which impacts their business competitiveness. This community service program aims to increase MSMEs' understanding, awareness, and interest in business digitalization and sustainable packaging innovation. This activity was carried out through educational seminars and interactive discussions involving 20 MSMEs from the culinary, handicraft, and service sectors. Evaluation was conducted using pre- and post-activity questionnaires to measure changes in participants' understanding and interest. Results showed an increase in participants' understanding of business digitalization from 30% to 85%, an increase in the use of social media for promotion from 20% to 45%, and an increase in interest in adopting environmentally friendly packaging from 15% to 70%. In addition, collaborative initiatives among MSMEs increased from 10% to 40%. However, direct implementation of these practices remains hampered by limited technical skills and access to supporting resources. These findings suggest that a participatory education approach is effective as a first step in strengthening the capacity of MSMEs and should be followed by ongoing technical assistance to ensure a sustainable impact.